ANALISIS POSTUR KERJA KARYAWAN DALAM PENGANGKATAN TABUNG GAS ELPIJI DARI CONVEYOR - Nadila, Mutia; Zetli, Sri (LPPM Universitas Putera Batam, 2021)
This firm still relies on physical labor to complete its tasks. Based on prior findings, it is anticipated that there may be instances where workers' work posture will be incorrect when doing duties in a bent position. Musculoskeletal Disorders (MSDs) can be caused by poor work posture. The goal of this study is to figure out how workers stand at work. REBA is the method that was employed. Pain was found in the waist, right wrist, left wrist, left calf, right calf, and back, according to the Nordic Body Map (NBM) questionnaire. Calculations were made using the REBA technique based on these data, and a score of 8 was obtained, putting it in the category of high danger and requiring rapid repair.